Soka Gakkai International in Post-Apartheid South Africa - Dessì, Ugo (Religions, 2020)
This paper analyzes the activities of Soka Gakkai International (SGI) in South Africa, a largely Christian country with the presence of very strong African Independent and Pentecostal churches, where Buddhism has mostly attracted the attention of a small minority of white middle-class people interested in meditational practices. By focusing on SGI South Africa, which has been able to reach out to a significant number of black, and, to a lesser extent, Coloured and Indian/Asian members, this ethnographic study aims to contribute to the understanding of Buddhism’s interplay with a broader cross-section of post-apartheid South African society, and, secondarily, to add to the existing literature on this Japanese new religious movement overseas. After a brief overview of the historical development of SGI in South Africa, my analysis focuses on SGI South Africa’s main ritual, social, and missionary activities; its interplay with local religions; its attempts to establish a meaningful link with South African culture; and, finally, on the religious experiences and narratives of SGI’s South African members.